2018
DOI: 10.1002/hep4.1259
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plasminogen Activator Inhibitor 1 Attenuates Hepatic Steatosis but Does Not Prevent Progressive Nonalcoholic Steatohepatitis in Mice

Abstract: Plasminogen activator inhibitor 1 (PAI‐1), an essential regulator of fibrinolysis, is increasingly implicated in the pathogenesis of metabolic disorders, such as obesity and nonalcoholic fatty liver disease (NAFLD). Pharmacologic inhibition of PAI‐1 is emerging as a highly promising therapeutic strategy for obesity and its sequelae. Given the well‐established profibrotic function of PAI‐1, we considered whether PAI‐1 may serve as a target for antifibrotic therapy in nonalcoholic steatohepatitis (NASH). We ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…We have previously shown that MCD diet-induced NASH is associated with marked induction OLIVARES And HEnKEL of hepatic ER stress as well as increased hepatic expression of Pai-1. 8,31 To establish whether this relationship is cause and effect, wild-type C57BL6/J mice were fed a MCD or methionine-and choline-sufficient (MCS) diet with or without the ER stress inhibitor, 4-phenylbutyric acid (4-PBA), for 14 days. Consistent with our previous observations in mice fed the MCD diet for 8 weeks, the livers of mice fed a MCD diet for 14 days showed activation of the UPR and significant induction of hepatic Pai-1 expression ( Figure 5).…”
Section: Inhibiting Er Stress Attenuates Pai-1 Induction In a Murinmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that MCD diet-induced NASH is associated with marked induction OLIVARES And HEnKEL of hepatic ER stress as well as increased hepatic expression of Pai-1. 8,31 To establish whether this relationship is cause and effect, wild-type C57BL6/J mice were fed a MCD or methionine-and choline-sufficient (MCS) diet with or without the ER stress inhibitor, 4-phenylbutyric acid (4-PBA), for 14 days. Consistent with our previous observations in mice fed the MCD diet for 8 weeks, the livers of mice fed a MCD diet for 14 days showed activation of the UPR and significant induction of hepatic Pai-1 expression ( Figure 5).…”
Section: Inhibiting Er Stress Attenuates Pai-1 Induction In a Murinmentioning
confidence: 99%
“…In particular, UPR dysfunction has been strongly linked to human metabolic diseases such as obesity, diabetes, and nonalcoholic fatty liver disease (NAFLD). [5][6][7][8][9][10][11][12][13] Plasminogen activator inhibitor-1 (PAI-1) is a stress-responsive gene that is in induced in response to tissue injury and serves a physiologic role in wound healing. Although best known for its function as an inhibitor of fibrinolysis, PAI-1 also regulates inflammation and fibrosis in numerous tissue types.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PAI‐1 levels have a higher correlation with liver fat content than visceral fat content 34 . In addition, prior work in murine models showing that PAI‐1‐deficient mice and wild type mice given a small molecular inhibitor of PAI‐1 were protected against diet‐induced steatosis formation 20‐22 further supports the hypothesis that PAI‐1 may be playing an important role in NAFLD pathophysiology.…”
Section: Discussionmentioning
confidence: 70%
“…Preclinical data supporting the biologic plausibility of PAI‐1 playing a causal role in the development of NAFLD include findings in a murine model exposed to a high fructose diet in which PAI‐1‐deficient mice were protected against the development of hepatic steatosis 20 . Furthermore, administration of a small molecule inhibitor of PAI‐1 attenuated high‐fat diet‐induced hepatic steatosis in two separate murine studies, 21,22 showing the potential to prevent NAFLD development with PAI‐1‐targeted therapies.…”
Section: Introductionmentioning
confidence: 98%